EDUCATIONAL VALUES IN CHILDREN’S STORIES, KELE STWIN AS A CASE STUDY - Hami, Bangeen Ibrahim; Tayib, Haval Salim (Journal of Duhok University, 2018)
The objective of this research is to clarify the educational values in children’s stories directed to a particular period of childhood, the research is under the title (Educational Values in Children’s Stories, Kele Stwin as a case study) which consist of five stories. These stories has been analyzed and evaluated especially the events that take place in the child’s environment and also the sentences and paragraphs of the stories in the research has been dissected and evaluated which became as a standard for these values. It has been realized in the results of this research that the cultural and knowledge values come first in the content of these stories and then followed by the social and moral values. Finally the recommendations come into this study is that it is very important to take into the consideration the importance of the content and value of the stories directed to the children because they have a very big rule in the development of their educational values in the child’s psychology according to the stages of childhood.